Pengaruh Museum Experience Terhadap Keputusan Berkunjung Kembali di Museum Geologi Bandung - Mulyana, Hadi; Edison, Emron (STIEPAR YAPARI Bandung, 2023)
This research aims to assess the impact of museum experience on the decision to revisit the Geological Museum of Bandung. A quantitative method was applied through Simple Linear Regression analysis, with a research sample consisting of 100 respondents, namely tourists who are currently visiting or have previously visited the Geological Museum of Bandung. Data from the questionnaire, structured on a Likert scale, were analyzed using SPSS to test the questionnaire instrument and the coefficient of determination. The results of the instrument testing show that each statement in the questionnaire is valid and reliable. Descriptively, the Museum Experience variable falls into the